Effect of Oral Clonidine on Hemodynamic Response During Surgery - Regmi, Bharati Sharma; Regmi, SR; Pradhan, B; Marahatta, MN; Dubey, L (Nepalese Heart Journal, 2013)
Clonidine is an alpha 2-adrenoceptor agonist. It has recently, however, found a new and possibly significant role in anaesthesia and the treatment of pain. Diazepam has been used as a drug for premedication for years but oral clonidine has not been used as premedication even though it is cheaper and has longer postoperative analgesic effect. This prospective, double blind randomized study was conducted in department of anaesthesiology, institute of medicine, TUTH. A total 60 consecutive patients scheduled for abdominal gynaecological surgeries were randomized to clonidine or diazepam premedication group and received these drug one hour before surgery planned under spinal anaesthesia. Intraoperative haemodynamic changes in terms of blood pressure, heart rate, oxygen saturation, were recorded. Hypotension was occurred in 9(15%) in clonidine group and 10(16.7%) in diazepam group, (p value> 0.05). During surgery, bradycardia was noted in 6(10%) vs. 3(5%) patient in diazepam and clonidine group respectively (p value >0.05). Nausea, shivering, restlessness were other side effects seen during surgery in both clonidine and diazepam group (33.33% vs. 36.66%). Although few more cases of nausea (1 vs. 5) with clonidine and few more cases of restless (3 vs. 7) were noted with diazepam , the overall difference was not statistically significant between two groups (p value >0.05). Oral clonidine premedication had similar hemodynamic response to diazepam. It is cheaper and has longer postoperative analgesic effect as well as similar sedative effect. Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 8-14 DOI: http://dx.doi.org/10.3126/njh.v7i1.8495